On the spectral properties of the one-dimensional Stark operator on the half-line - Makhmudova, M. G.; Khanmamedov, A. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.9We consider a one-dimensional Stark operator on a half-line with the Dirichlet boundary condition at zero. The asymptotic behavior of the eigenvalues at infinity is found.